(untitled) (Palíndromo, 2023)
It is necessary to chew letters to feel sentences and spit out words to compose artistic practices with the text: based on this dynamic, the publication “e s c r i t a s” presents itself as an experimental compilation of texts in electronic format (e-book). The proposal was developed based on virtual meetings during the COVID-19 pandemic. They are “e s c r i t a s” with spaces, as they are “letters in social distancing” tensioning relationships between a slow return to post-pandemic “normality” and the desire to inhabit new art production platforms. This report aims to describe the experience of a collaborative creative process and disseminate how experimental proposals in writing can find support in public notices. The article follows a narrative approach when recalling the processes of making the work, using image reproductions of the publication itself. The concept of intercessors proposed by Deleuze is also aligned when relating the creation proposals in workshops and in the text to a multiplicity of agencies, glimpsing the other through the difference in their productions, through the unlikely ways of coming and going, creating a work composed of affections that pause in stories, poems, texts, in short, in writings.